DEVELOPING A FRAMEWORK FOR THE INTEGRATION OF 21ST CENTURY LEARNING AND INNOVATION SKILLS INTO PRE-SERVICE ELT TEACHERS' PRACTICUM - Hasan Bedir (Informascope, 2019)
Research has shown that teacher education programs are ineffective in preparing teachers for 21st century skills so there exists a need for professional development to improve teachers' knowledge and practices which improve student learning outcomes. Teachers' Professional Development (PD) has been intriguing researchers in the 21st first century more than the previous century since the skills students need to learn in preparation for further education are more sophisticated in this century. This paper aimed to develop a framework to integrate 21st century learning and innovation skills (4Cs) into pre-service ELT teacher education curriculum framework for 21st century learning and skills. The framework was developed through a full evaluation of the related research and analysis of a 12-week teaching practicum data. It was intended to be a guide for those who are developing professional development programs for 21st century skills. The developmental process revealed positive casual relations between the framework developed and the probability of having positive and significant results. Regarding the focus of the framework, we also observed more positive outcomes for the intervention of 21st century skills, mainly learning and innovation skills due to the active participation of the pre-service teachers.